2003
DOI: 10.1046/j.1365-2389.2003.51309.x
|View full text |Cite
|
Sign up to set email alerts
|

Life‐Sustaining Treatments: What Do Physicians Want and Do They Express Their Wishes to Others?

Abstract: This survey of physicians calls attention to the gap between preferences for medical care at the end of life and expressing wishes to others through discussion and advance directives, even among physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 47 publications
3
58
2
3
Order By: Relevance
“…This fi nding is similar to the previous literature, which reported that doctors and nurses predominantly wished to forgo high-intensity treatment or resuscitation and opted for comfort care at end-of-life. (12)(13)(14)(15) This fi nding also explained the correlation in the present study between age and preference for CPR and symptom relief treatment, as the doctors and nurses in this study were generally younger than the patients and relatives. The discrepancy could be due to the fact that doctors and nurses may have realised, through exposure, that aggressive treatment does not always change the ultimate outcome for a functionimpaired patient and only results in more suffering instead of benefi ts.…”
Section: Discussionsupporting
confidence: 72%
“…This fi nding is similar to the previous literature, which reported that doctors and nurses predominantly wished to forgo high-intensity treatment or resuscitation and opted for comfort care at end-of-life. (12)(13)(14)(15) This fi nding also explained the correlation in the present study between age and preference for CPR and symptom relief treatment, as the doctors and nurses in this study were generally younger than the patients and relatives. The discrepancy could be due to the fact that doctors and nurses may have realised, through exposure, that aggressive treatment does not always change the ultimate outcome for a functionimpaired patient and only results in more suffering instead of benefi ts.…”
Section: Discussionsupporting
confidence: 72%
“…Some people want more care (even if the evidence suggests that it may not be beneficial), whereas others will want less care or interventions when the prospects for life become constrained or limited. There is a disparity in what physicians profess they want for their own end-of-life care and what is offered to their patients (7)(8)(9). Based on studies in older as well as younger physicians from different cultural backgrounds, between 80% and 88.3% prefer to receive pain medication but would refuse or forego life-sustaining treatments at the end of life.…”
Section: Framing the Issues And Scope Of Workmentioning
confidence: 99%
“…In addition, more than 80% of these physicians indicated that the EOL care they would select was to receive pain medication, but refuse life-sustaining medical treatments. 15 In a 2011 essay titled "How Doctors Die," a retired family practice physician described why physicians administer so much care to patients at the end of their lives that they would not want for themselves. 16 His explanations for their aggressive EOL treatment included patients who have not made their wishes known, overwhelmed families who request that everything be done, expectations of outcomes that may be misguided or unrealistic, physicans attempting to address patient or family wishes or to minimize potential for litigation, as well as possible exploitation to earn higher fees.…”
Section: Attitude Toward and Disregard Of Advance Directives By Physimentioning
confidence: 99%